Syntheses, characterization, crystal structures and Jack bean urease inhibitory property of NiII, CdII, CuII and FeIII complexes with bis-Schiff bases. (1st February 2023) - He, Baihui; Dong, Change; Wang, Xiaoqing; Cao, Yan; Gao, Yuanze; Yang, Mingming; Zhang, Jiahui; Jing, Changling; Shi, Dahua; You, Zhonglu
Graphical abstract: Four new nickel(II), cadmium(II), copper(II) and iron(III) complexes were prepared. The structures of the complexes were characterized by single crystal X-ray diffraction. The Jack bean urease inhibitory assay indicated that the copper complex has remarkable activity. Abstract: Four new nickel(II), cadmium(II), copper(II) and iron(III) complexes, [Ni3 (L 1 )2 ( μ 2 - η 1 : η 1 -CH3 COO)2 ] (1 ), [Cd2 (L 1 )2 (CH3 OH)2 ] (2 ), [Cu(L 2 )] (3 ) and [Fe2 (L 3 )2 ( μ 2 -OCH3 )2 ] (4 ), where L 1, L 2 and L 3 are the dianionic form of N, N' -bis(5-fluorosalicylidene)-1, 3-propanediamine (H2 L 1 ), N, N' -bis(3, 5-difluorosalicylidene)-1, 3-propanediamine (H2 L 2 ) and N, N' -bis(4-fluorosalicylidene)-1, 3-propanediamine (H2 L 3 ), respectively, were prepared. The compounds have been characterized by physico-chemical methods. The structures of the metal complexes were also confirmed by single crystal X-ray diffraction. The Ni atoms in complex 1 are in square pyramidal and octahedral coordination environments. The Cd atoms in complex 2 are in an octahedral coordination environment. The Cu atom in complex 3 is in a tetrahedrally distorted square planar coordination environment. The Fe atoms in complex 4 are in an octahedral coordination environment. The Jack bean urease inhibitory assay indicated that the copper complex displays good activity.